Diffuse Nodular Lymphoid Hyperplasia of Colon in a Child- A Case Report with Review of Literature - Chikkanaganna Pillavenkataswamy Manjula; Belur Venugopal Suguna; SR Niveditha; Sreedhar Murthy (Journal of Clinical and Diagnostic Research, 2017)
Diffuse Nodular Lymphoid Hyperplasia (DNLH) of the Gastrointestinal Tract (GIT) is an uncommon, benign reactive lesion occurring in all age groups. It is seen distributed throughout the GIT. DNLH is characterized by diffuse mucosal polypoid masses of 2-5 mm diameter. Commonly mistaken for various polyposis syndromes on endoscopy, It may present with abdominal pain, recurrent hematochezia, intussusception, intestinal obstruction and anaemia. Childhood DNLH is associated with various etiologies from food hypersensitivity to immunodeficiency syndromes. As DNLH is mostly a benign, reactive process, histopathology plays an important role in its recognition to prevent misdiagnosis and radical procedures. Here, we present a rare case of DNLH of colon in a two year old female child, presenting with abdominal distension. Colonoscopy revealed multiple colonic polyps. Total colectomy specimen revealed multiple, sessile polyps of 0.2 to 0.3cm carpeting the entire colonic mucosa. Microscopy revealed polyps comprised of lymphoid follicles with germinal centre in the mucosal and submucosal location.